The use of online meeting platforms for information literacy training by academic librarians: the case of a private higher education institution academic library - Mambo, Rumbidzai (Department of Knowledge and Information Stewardship, 2025)
The study's objective was to understand the competencies required by academic librarians in using online meeting platforms for enhancing postgraduate students' information searching, retrieval and use skills to meet their information needs. The following research questions were generated to address the objective, What competencies are required by academic librarians to deliver information literacy training using online meeting platforms?; What competencies do the academic librarians of the selected higher education institution currently possess for delivering information literacy training via online means? and What challenges (if any) are the academic librarians of the selected higher education institution facing in providing postgraduate students with online information literacy training to meet their information needs? The study was supported by Wilson's (1999) theory of information behaviour. A multi-method approach was used, and a case study employed to investigate the competencies of academic librarians using online meeting platforms for information literacy sessions at a private higher education institution. The target population included Institution X academic librarians and postgraduate students. Purposive sampling was adopted for the researcher to interview specifically librarians who provide postgraduate students' information literacy sessions to meet their information needs. A census was used to ascertain trends among postgraduate students regarding information literacy training using online platforms to meet their information needs. Data was collected via semi-structured interviews using Microsoft Teams with librarians and an online structured questionnaire for postgraduate students using Google Forms. In concluding, the study presents, inter alia, a blend of librarians' competencies which include knowledge, skills and attributes required to deliver online information literacy training to meet the information needs of postgraduate students in the current digital era. It recommends, inter alia, that institutions of higher learning could benefit from the outcomes of this study in terms of continuous upskilling of academic librarians to ensure postgraduate students are provided with relevant online information literacy training for enhanced academic performance.